OPTIMIZING THE ROLE OF GUIDANCE AND COUNSELING IN DEALING WITH CAREER CHOICE ANXIETY AMONG HIGH SCHOOL STUDENTS - Jovita Anindya; Mamat Supriatna; Nadia Aulia Nadhirah; Tiara Iskandar Pratiwi (Study Program Guidance and Counseling, Univesitas Pendidik, 2024)
Schools are important role in preparing students to face their future, but students often experience anxiety when deciding about their careers. This study aims to identify career problems encountered by students and see the role of Guidance and Counseling teachers in helping students overcome this anxiety. The research method used was a quantitative approach with data collection using a questionnaire given to 78 students of grade XI high school in Bogor Regency. The results showed that most students experienced a moderate level of career problems. The most prominent aspect is career choice anxiety, where students feel fear and anxiety in making decisions about the career that will be undertaken. To overcome anxiety in career selection, this study recommends using several strategies or techniques by counseling teachers. These strategies include the application of group guidance techniques, modeling techniques, and individual counseling.